Energy production revolution in China during 2015–2019: progress and challenges. Issue 1 (2nd January 2023) - Li, Hui; Zhang, Ruining; Zhang, Lingyue; Qin, Yu; Liao, Hua
ABSTRACT: Since the release of the Energy Supply and Consumption Revolution Strategy (2016–2030), China has made remarkable advancements. This paper establishes an evaluation system to analyze the progress of the energy production revolution in China during 2016–2019. The results report that more than three-fourths of the indicators fulfill the process schedule by more than 80% in 2019. Specifically, the clean development and efficient utilization of coal is carried out significantly among the five major areas of the energy production revolution. However, China's energy production revolution still faces challenges, such as insufficient technology innovation of power generation, weak consumption and storage capacity of clean energy, the outdated transaction management system of the energy market, the limited emergency capacity of the energy system, and the backward construction of an energy production intelligent system. Finally, policy implications for accelerating the energy production revolution are proposed.